Composite electrolyte for secondary metal battery as well as preparation method and application of composite electrolyte
By adding amino acid additives to the aqueous zinc salt electrolyte, the double layer on the zinc anode surface is altered, solving the problem of zinc dendrite growth and achieving high efficiency, stability, and long lifespan for zinc-ion batteries.
Patent Information
- Application Number
- CN202410568787.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-09
- Publication Date
- 2025-11-11
AI Technical Summary
The desolvation of zinc ions in aqueous solution generates hydrogen gas and byproducts, leading to the growth of zinc dendrites, which affects battery life and coulombic efficiency. Existing technologies are unable to effectively suppress this process.
Adding amino acid additives with different isoelectric points to aqueous zinc salt electrolytes alters the electric double layer on the zinc anode surface through electrostatic adsorption, thereby inhibiting dendrite growth and side reactions and increasing the zinc ion migration rate.
It significantly improves the corrosion resistance and cycle stability of zinc anodes, extends battery life, and enhances electrochemical performance, cycle stability, and coulombic efficiency.
Smart Images

Figure CN120933509A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of secondary metal battery technology, and in particular to an aqueous composite electrolyte containing amino acid additives, its preparation method, and its application. Background Technology
[0002] Zinc metal batteries, as a new type of rechargeable battery, have gained widespread favor among researchers. Compared with other batteries, they have the following advantages: (1) high energy density and high power density, (2) environmental friendliness, (3) abundant and inexpensive resources on the earth's surface, and (4) relatively low redox potential (-0.76V compared to the standard hydrogen electrode). Their excellent performance has also demonstrated broad application prospects in many portable electronic device industries, and they are expected to become a candidate for large-scale energy storage in the future.
[0003] However, zinc ions exist in aqueous solution as hydrated zinc ions. During desolvation, free water molecules and active water molecules generated during desolvation adsorb onto the zinc anode surface, competing with zinc ions for electrons to produce hydrogen gas, thus increasing the electrolyte pH. Simultaneously, the hydrogen evolution reaction produces water-insoluble and insulating byproducts that passivate the electrode surface and alter the electrolytic surface morphology. This uneven electrode surface leads to disordered zinc ion flux and uneven local current density, promoting zinc dendrite growth, reducing coulombic efficiency, and significantly impacting battery life, thereby severely hindering the further large-scale application of aqueous zinc-ion batteries. Just as water can both support and capsize a battery, the presence of solvent water in the electrolyte, while significantly enhancing zinc ion migration, inevitably leads to the solvation structure of hydrated zinc ions, causing side reactions. Therefore, altering the solvation structure of zinc ions and suppressing the activity of free water molecules and desolvated water molecules is crucial for inhibiting side reactions and improving the lifespan of aqueous zinc-ion batteries. Summary of the Invention
[0004] This invention provides an aqueous composite electrolyte containing amino acid additives, its preparation method, and its application, with the aim of solving the aforementioned problems existing in the background art.
[0005] To achieve the above objectives, this invention prepares a composite electrolyte by adding amino acid additives to an aqueous electrolyte containing zinc salt solute. Since the pH of conventional aqueous zinc salt electrolytes is mostly neutral or weakly acidic, amino acids with different isoelectric points have varying abilities to dissociate into cations and anions in aqueous zinc salt electrolytes, thus producing different degrees of improvement. In neutral or weakly acidic environments, the amino acid additives undergo different degrees of dissociation due to their different isoelectric points, producing different numbers of cations or anions. Among these, ammonium ions will dissociate as -NH4 or -NH3. + It exists in the form of -COOH or -COO. -However, any combination of the above forms can effectively improve the solvation structure of zinc ions in the electrolyte, enabling amino acid molecules to achieve electrostatic adsorption on the zinc anode. Thus, even with trace amounts added, it can still cause the enrichment of additive functional molecules in the electric double layer, accelerate zinc ion kinetics, and inhibit dendrite growth and side reactions.
[0006] The embodiments of the present invention provide a method for preparing an aqueous composite electrolyte containing amino acid additives, comprising the following steps:
[0007] S1. Add soluble zinc salt to deionized water to prepare an aqueous zinc salt electrolyte.
[0008] S2. After the pH value of the aqueous zinc salt electrolyte stabilizes, gradually add the amino acid additive, stir continuously until completely dissolved, let stand, and obtain an aqueous composite electrolyte containing the amino acid additive.
[0009] Furthermore, the soluble zinc salt is any one of zinc sulfate, zinc chloride, zinc nitrate, zinc acetate, zinc trifluoromethanesulfonate, zinc perchlorate, zinc trifluoromethanesulfonylimide, and zinc tetrafluoroborate.
[0010] Furthermore, the concentration of the soluble zinc salt is 0.3–12 mol / L.
[0011] The amino acid additive is any one of glycine, alanine, valine, leucine, isoleucine, methionine, proline, tryptophan, serine, tyrosine, cysteine, phenylalanine, asparagine, glutamine, threonine, glutamic acid, lysine, arginine, and histidine.
[0012] The concentration of the amino acid additive is 0.01–2 mol / L.
[0013] The aqueous composite electrolyte containing amino acid additives has a pH value of 1.9 to 5, preferably 2 to 4.5.
[0014] Based on the same inventive concept, embodiments of the present invention also provide a battery comprising an aqueous composite electrolyte containing amino acid additives obtained by the above preparation method.
[0015] Furthermore, the aqueous composite electrolyte containing amino acid additives and commercial zinc foil are assembled into a symmetrical battery; or the aqueous composite electrolyte containing amino acid additives and commercial current collectors are assembled into a half-cell; or the aqueous composite electrolyte containing amino acid additives is used as the electrolyte, commercial zinc foil as the negative electrode, and CNT / MnO2, V2O5 or Prussian blue as the positive electrode to assemble an aqueous zinc-ion battery.
[0016] Furthermore, the commercial current collector is any one of titanium foil, copper foil, nickel foil, stainless steel mesh, copper mesh, nickel mesh, copper foam, and nickel foam.
[0017] The above-described solution of the present invention has the following beneficial effects:
[0018] (1) Conventional aqueous zinc salt electrolytes have a neutral to weakly acidic pH. Amino acids with different isoelectric points have varying abilities to dissociate into cations and anions in aqueous zinc salt electrolytes, resulting in different degrees of improvement. Amino acid additives, in neutral or weakly acidic environments, will dissociate to varying degrees due to their different isoelectric points, producing different quantities and types of cations or anions. Among these, ammonium ions will dissociate as -NH4 or -NH3. + It exists in the form of -COOH or -COO. - Form. Importantly, in the weakly acidic environment of conventional aqueous soluble zinc salt electrolytes, amino acids with higher isoelectric points will more readily adopt the form -NH3. + It exists in the form of -COOH. Among them, -NH3... + They can electrostatically adsorb onto the surface of the zinc anode, altering the electric double layer structure and preventing the adsorption and electrolysis of free water molecules. -NH4, -COOH, and -COO - All of these methods can alter the solvation structure of hydrated zinc ions, reduce the coordination number, and decrease the release of active water molecules during desolvation. Furthermore, the use of amino acid additives significantly increases the migration rate of zinc ions, effectively achieving stable and reversible zinc deposition / dissolution. Therefore, the higher the isoelectric point of the amino acid, the stronger the electrochemical performance and stability of the aqueous composite electrolyte described in this invention.
[0019] (2) The aqueous composite electrolyte containing amino acid additives in this invention exhibits extremely strong stability and significantly improves the corrosion resistance and cycle stability of the zinc anode. It is suitable for long-term storage and use in commercial aqueous zinc-ion battery electrolytes, enhancing the electrochemical performance and cycle stability of the zinc anode at up to 5 mA cm⁻¹. -2 At current density, the half-cell cycle length exceeds 200 cycles, and the symmetrical cell cycle length exceeds 700 hours, at a conventional 1mA cm⁻¹ current density. -2 Current density and 1 mA cm -2 Under capacity testing conditions, the lifespan exceeds 4100 hours, far surpassing existing composite electrolytes using amino acid additives, effectively improving the performance of secondary zinc metal batteries. Attached Figure Description
[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 The coulombic efficiency test curves of the half-cell assembled with commercial zinc sheet and titanium foil of the present invention, aqueous composite electrolyte containing arginine obtained in Example 1, and 2M zinc sulfate aqueous solution are shown.
[0022] Figure 2 The symmetrical battery assembled from the commercial zinc sheet of the present invention, the aqueous composite electrolyte containing arginine obtained in Example 1, and a 2M zinc sulfate aqueous solution, operates at a current density of 5 mA / cm². -2 Time-voltage comparison graph for cyclic stability testing;
[0023] Figure 3 The symmetrical battery assembled from the commercial zinc sheet of the present invention, the aqueous composite electrolyte containing arginine obtained in Example 1, and a 2M zinc sulfate aqueous solution, operates at a current density of 1 mA / cm². -2 Time-voltage comparison graph for cyclic stability testing;
[0024] Figure 4 This is a time-voltage comparison graph of the cycle stability test of the commercial zinc sheet of the present invention and the symmetric battery assembled with the aqueous composite electrolyte containing tryptophan and 2M zinc sulfate aqueous solution obtained in Example 2.
[0025] Figure 5 This is a time-voltage comparison graph of the cycle stability test of the commercial zinc sheet of the present invention and the symmetric battery assembled with an aqueous composite electrolyte containing glutamic acid and a 2M zinc sulfate aqueous solution obtained in Example 3.
[0026] Figure 6 This is a time-voltage comparison graph of the cycle stability test of a symmetrical battery assembled with the commercial zinc sheet of the present invention, the aqueous composite electrolyte containing arginine and without pH adjustment obtained in Comparative Example 1, and the aqueous composite electrolyte containing arginine obtained in Example 1.
[0027] Figure 7 This is a time-voltage comparison graph of the cycle stability test of a symmetrical battery assembled with the commercial zinc sheet of the present invention, the aqueous composite electrolyte containing choline obtained in Comparative Example 2, and the aqueous composite electrolyte containing arginine obtained in Example 1.
[0028] Figure 8This is a time-voltage comparison graph of the cycle stability test of a symmetrical battery assembled with the commercial zinc sheet of the present invention, the aqueous composite electrolyte containing aspartic acid obtained in Comparative Example 3, and the aqueous composite electrolyte containing arginine obtained in Example 1. Detailed Implementation
[0029] To make the technical problems, technical solutions and advantages of the present invention clearer, a detailed description will be given below in conjunction with the accompanying drawings and specific embodiments.
[0030] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.
[0031] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.
[0032] Zinc ions exist in aqueous solution as hydrated zinc ions. During desolvation, free water molecules and active water molecules generated during desolvation adsorb onto the zinc anode surface. They compete with zinc ions for electrons, producing hydrogen gas and increasing the electrolyte pH. Simultaneously, the hydrogen evolution reaction generates water-insoluble and insulating byproducts that passivate the electrode surface and alter the electrolytic surface morphology. This uneven electrode surface leads to disordered zinc ion flux and uneven local current density, promoting zinc dendrite growth, reducing coulombic efficiency, and significantly impacting battery life. Consequently, this severely hinders the further large-scale application of aqueous zinc-ion batteries.
[0033] This invention addresses existing problems by providing an aqueous composite electrolyte containing amino acid additives, its preparation method, and its applications.
[0034] The embodiments of the present invention provide a method for preparing an aqueous composite electrolyte containing amino acid additives, comprising the following steps:
[0035] S1. Add soluble zinc salt to deionized water to prepare an aqueous zinc salt electrolyte.
[0036] S2. After the pH value of the aqueous zinc salt electrolyte stabilizes, gradually add the amino acid additive, stir continuously until completely dissolved, let stand, and obtain an aqueous composite electrolyte containing the amino acid additive.
[0037] Furthermore, the soluble zinc salt is any one of zinc sulfate, zinc chloride, zinc nitrate, zinc acetate, zinc trifluoromethanesulfonate, zinc perchlorate, zinc trifluoromethanesulfonylimide, and zinc tetrafluoroborate.
[0038] Furthermore, the concentration of the soluble zinc salt is 0.3–12 mol / L.
[0039] The amino acid additive is any one of glycine, alanine, valine, leucine, isoleucine, methionine, proline, tryptophan, serine, tyrosine, cysteine, phenylalanine, asparagine, glutamine, threonine, glutamic acid, lysine, arginine, and histidine.
[0040] The concentration of the amino acid additive is 0.01–2 mol / L.
[0041] The aqueous composite electrolyte containing amino acid additives has a pH value of 1.9 to 5, preferably 2 to 4.5.
[0042] Based on the same inventive concept, embodiments of the present invention also provide a battery comprising an aqueous composite electrolyte containing amino acid additives obtained by the above preparation method.
[0043] Furthermore, the aqueous composite electrolyte containing amino acid additives and commercial zinc foil are assembled into a symmetrical battery; or the aqueous composite electrolyte containing amino acid additives and commercial current collectors are assembled into a half-cell; or the aqueous composite electrolyte containing amino acid additives is used as the electrolyte, commercial zinc foil as the negative electrode, and CNT / MnO2, V2O5 or Prussian blue as the positive electrode to assemble an aqueous zinc-ion battery.
[0044] Furthermore, the commercial current collector is any one of titanium foil, copper foil, nickel foil, stainless steel mesh, copper mesh, nickel mesh, copper foam, and nickel foam.
[0045] Example 1
[0046] First, prepare zinc sulfate electrolyte by adding 17.2536g of zinc sulfate heptahydrate to 12.44mL of deionized water and stirring continuously until the solution is clear and the pH no longer changes (approximately 3.45) to obtain a 3mol / L zinc sulfate aqueous solution.
[0047] Add 0.1 mol / L arginine powder (isoelectric point = 10.7) to the above zinc sulfate aqueous solution, stir rapidly until the powder dissolves, adjust the pH to 4, and let stand for 3 hours to obtain a stable aqueous composite electrolyte containing arginine.
[0048] Example 2
[0049] This embodiment is a parallel experiment similar to that of Example 1, except that arginine is replaced with tryptophan (isoelectric point = 5.89), and the other preparation methods are exactly the same as those in Example 1, to obtain an aqueous composite electrolyte containing lysine.
[0050] Example 3
[0051] This embodiment is a parallel experiment similar to that of Example 1, except that arginine is replaced with glutamic acid (isoelectric point = 3.22), and the other preparation methods are exactly the same as those in Example 1, to obtain an aqueous composite electrolyte containing glutamic acid.
[0052] Comparative Example 1
[0053] This embodiment is a parallel experiment similar to that of Example 1. 0.1 mol / L arginine powder is added and stirred rapidly until the powder dissolves, but the pH value of the solution is not adjusted. The pH value can reach 5.2. Other preparation methods are exactly the same as those in Example 1 to obtain an aqueous composite electrolyte containing arginine.
[0054] Comparative Example 2
[0055] This comparative example was conducted in parallel with Example 1, using choline as the additive. Choline contains NH3. + The group contains no carboxyl group, to demonstrate the presence of NH3 in the zwitterion of the quaternary ammonium salt. + The strong synergistic effect of the carboxyl group, and the other preparation methods are exactly the same as in Example 1, yields a product containing NH3. + Aqueous composite electrolyte.
[0056] Comparative Example 3
[0057] This embodiment is a parallel experiment similar to that of Example 1, except that arginine is replaced with aspartic acid (isoelectric point = 2.77), and the other preparation methods are exactly the same as those in Example 1, to obtain an aqueous composite electrolyte containing aspartic acid.
[0058] Performance testing:
[0059] Commercial zinc sheets were used as the negative electrode, and commercial titanium foil as the positive electrode. Half-cells were assembled using the aqueous composite electrolyte containing arginine obtained in Example 1 and the 2M zinc sulfate aqueous solution electrolyte, respectively, for electrochemical testing. The results are as follows: Figure 1 As shown, at 5mA cm -2 After discharging at a current density of 5 mA for 48 minutes, the electrolyte was charged to 0.5 V, and cycle stability was tested. Commercial zinc sheets exhibited superior cycle performance in the aqueous composite electrolyte containing amino acid additives obtained in Example 1 of this invention, at 5 mA cm⁻¹. -2 It can stably cycle ≥200 times at a current density and has a coulombic efficiency of up to 98.28%. Using commercial zinc sheets as the negative electrode, symmetrical cells were assembled using the aqueous composite electrolyte containing amino acid additives obtained in Example 1 of this invention and the 2M zinc sulfate aqueous solution electrolyte, respectively, for electrochemical testing. The results are as follows: Figure 2 As shown, at 5mAcm -2The zinc anode was continuously charged and discharged for 1 hour each at a current density of 5 mA cm⁻¹, and its cycle stability and cycle life in the electrolyte were tested. The commercial zinc sheet exhibited superior cycle stability and cycle life in the aqueous composite electrolyte containing amino acid additives obtained in Example 1 of this invention. -2 It can be stably cycled for ≥700h at a current density.
[0060] Commercial zinc sheets were used as the negative electrode. Symmetrical cells were assembled using the aqueous composite electrolyte containing arginine obtained in Example 1 of this invention and the 2M zinc sulfate aqueous solution electrolyte, respectively, and electrochemical tests were performed. The results are as follows: Figure 3 As shown, at 1mA cm -2 The zinc anode was continuously charged and discharged for 1 hour each at a current density of 1 mA cm⁻¹, and its cycle stability and cycle life in the electrolyte were tested. The commercial zinc sheet exhibited superior cycle stability and cycle life in the aqueous composite electrolyte containing amino acid additives obtained in Example 1 of this invention, at 1 mA cm⁻¹. -2 It can be stably cycled for ≥4100h at a current density.
[0061] Commercial zinc sheets were used as the negative electrode. Symmetrical cells were assembled using the aqueous composite electrolyte containing tryptophan obtained in Example 2 of this invention and the 2M zinc sulfate aqueous solution electrolyte, respectively, and electrochemical tests were performed. The results are as follows: Figure 4 As shown, under the same test conditions, the cycle time often exceeds 600h, which is similar to the results in Example 1, and still has excellent cycle performance that significantly surpasses that of aqueous zinc sulfate electrolyte.
[0062] Commercial zinc sheets were used as the negative electrode. Symmetrical cells were assembled using the aqueous composite electrolyte containing glutamate obtained in Example 3 of this invention and the 2M zinc sulfate aqueous solution electrolyte, respectively. Electrochemical tests were then performed, and the results are as follows: Figure 5 As shown, under the same test conditions, the cycle time often exceeds 500h, which is similar to the results in Example 1, and still has excellent cycle performance that significantly surpasses that of aqueous zinc sulfate electrolyte.
[0063] Commercial zinc sheets were used as the negative electrode. Symmetrical cells were assembled using the aqueous composite electrolyte containing arginine obtained in Example 1 of this invention and the aqueous composite electrolyte containing arginine without pH adjustment obtained in Comparative Example 1, respectively. The results are as follows: Figure 6 As shown, under the same test conditions, the cycle life of a symmetrical battery assembled with an aqueous composite electrolyte without pH adjustment is only about 400 hours. This is because the pH of the unadjusted composite electrolyte can reach 5.4. The excessively high pH weakens the hydrolysis of amino acids in an acidic environment and exacerbates the corrosion of the zinc anode in the aqueous electrolyte.
[0064] Commercial zinc sheets were used as the negative electrode. Symmetrical cells were assembled using the aqueous composite electrolyte containing arginine obtained in Example 1 of this invention and the aqueous composite electrolyte containing choline obtained in Comparative Example 2, respectively, and electrochemical tests were performed. The results are as follows: Figure 7 As shown, under the same test conditions, the cycle life of a symmetrical battery assembled with an aqueous composite electrolyte containing choline is only about 230 hours. This is because of the lack of NH3. + The strong synergistic effect of the carboxyl group shows significantly poor cycling stability. The lack of carboxyl group effect results in poor solvation structure change of zinc ions in aqueous solution, which cannot fundamentally accelerate zinc ion dynamics and inhibit competitive electron plundering by water molecules.
[0065] Commercial zinc sheets were used as the negative electrode. Symmetrical cells were assembled using the aqueous composite electrolyte containing arginine obtained in Example 1 of this invention and the aqueous composite electrolyte containing aspartic acid obtained in Comparative Example 3, respectively, and the results are as follows: Figure 8 As shown, under the same test conditions, the cycle life of a symmetrical battery assembled with an aqueous composite electrolyte containing aspartic acid is only about 200 hours. This is because the extremely low isoelectric point of aspartic acid (isoelectric point = 2.77) leads to a low NH4+ content in the weakly acidic aqueous electrolyte of the pH specified in this invention. 3+ Most of it is converted to NH 4+ The presence of amino acids in certain forms leads to a decrease in their adsorption capacity at the negative electrode. Furthermore, with a small amount added, a strong additive stable protective layer cannot be formed, resulting in a reduced lifespan.
[0066] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a composite electrolyte, characterized in that, Includes the following steps: S1. Add soluble zinc salt to deionized water to prepare an aqueous zinc salt electrolyte. S2. After the pH of the aqueous zinc salt electrolyte stabilizes, gradually add the amino acid additive, stir continuously until completely dissolved, let stand, and obtain an aqueous composite electrolyte containing the amino acid additive.
2. The preparation method according to claim 1, characterized in that, The soluble zinc salt is any one of zinc sulfate, zinc chloride, zinc nitrate, zinc acetate, zinc trifluoromethanesulfonate, zinc perchlorate, zinc trifluoromethanesulfonyl imide, and zinc tetrafluoroborate.
3. The preparation method according to claim 1, characterized in that, The amino acid additive is any one of glycine, alanine, valine, leucine, isoleucine, methionine, proline, tryptophan, serine, tyrosine, cysteine, phenylalanine, asparagine, glutamine, threonine, glutamic acid, lysine, arginine, and histidine.
4. The preparation method according to claim 1, characterized in that, The concentration of the soluble zinc salt is 0.3–12 mol / L.
5. The preparation method according to claim 1, characterized in that, The concentration of the amino acid additive is 0.01–2 mol / L.
6. The preparation method according to claim 1, characterized in that, The aqueous composite electrolyte containing amino acid additives has a pH value of 1.9–5.
7. An aqueous composite electrolyte containing amino acid additives, characterized in that, The aqueous composite electrolyte containing amino acid additives is prepared by the preparation method described in any one of claims 1 to 6.
8. A battery, characterized in that, The aqueous composite electrolyte containing amino acid additives prepared by the preparation method according to any one of claims 1 to 6, or the aqueous composite electrolyte containing amino acid additives according to claim 7.
9. The battery according to claim 8, characterized in that, A symmetrical battery is assembled from the aqueous composite electrolyte containing amino acid additives and commercial zinc foil; or a half-cell is assembled from the aqueous composite electrolyte containing amino acid additives and commercial current collector; or a secondary zinc metal battery is assembled from the aqueous composite electrolyte containing amino acid additives as the electrolyte, commercial zinc foil as the negative electrode, and CNT / MnO2, V2O5 or Prussian blue as the positive electrode.
10. The battery according to claim 9, characterized in that, The commercial current collector is any one of titanium foil, copper foil, nickel foil, stainless steel mesh, copper mesh, nickel mesh, copper foam, and nickel foam.
Citation Information
Cited By
Mixed aqueous electrolyte containing long-chain fatty acid zinc salt and application thereof
CN122000496A